Ответы и объяснения

Лучший Ответ!
2012-04-21T16:27:41+00:00

 (2x-6)(-3x+5)=0 

  -6х^2+10х+18х-30=0

 -6x2 + 28x - 30 = 0

-6x2 + 28x - 30 = 0
Делим на 2:
-3x2 + 14x - 15 = 0
D = b2 - 4ac
D = 196 - 180 = 16 = 4^2

x1,2 = -b ± √D/2a
x1 = -14 + 4/-6= 10/-6 = 1.6
x2 = -14 - 4/-6 = 18/6= 3
Ответ: x1 = 1.6 ; x2 = 3

 

 

  (-2x+3)(6+3x)=0

   -12x-6x^2+18+9x=0

    -6x2 - 3x + 18 = 0
-6x2 - 3x + 18 = 0
Делим на 3:
-2x2 - x + 6 = 0
D = b2 - 4ac
D = 1 + 48 = 49 = 7^2

x 1,2= -b± √D/2a
x1 = 1 + 7/-4=-2
x2 = 1 - 7/-4=1.5
Ответ: x1 = -2 ; x2 = 1.5

2012-04-21T16:48:52+00:00

1)(2x-6)(-3x+5)=0

 -6x^2+10x+18x-30=0

 -6x^2+28x-30=0

  D=28^2-4*(-6)*(-30)=784-720=64

  X1=(-28-8)/(-12)=-36/-12=3

  X2=(-28+8)/(-12)=-20/-12=1.6

 

2)-12x-6x^2+18+9x=0

   -3x-6x^2+18=0

   -6x^2-3x+18=0

    D=3^2-4*(-6)*18=9+432=441

    X1=(3-21)/(-12)=-18/-12=1.5

    X2=(3+21)/(-12)=24/-12=-2